2019
DOI: 10.1155/2019/2763093
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid and Non-Alcoholic Fatty Liver Disease according to Different Menstrual Status Groups

Abstract: Objective The present study aimed to explore the association between SUA and NAFLD in women with different menstrual statuses. Methods A total of 6043 women were selected from the Jidong and Kailuan communities for inclusion in the present study. The SUA levels of participants were divided into quartiles. NAFLD was determined by abdominal ultrasonography. Data from laboratory tests and clinical examination were collected, and basic information was obtained from standardized questionnaires. The menstrual status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…22 Abdominal ultrasonography found at least two manifestations that could diagnose NFALD, including diffusely increased echogenicity (''bright'') liver with liver echogenicity greater than kidney or spleen, vascular blurring, and deep attenuation of ultrasound signal. 23…”
Section: Methodsmentioning
confidence: 99%
“…22 Abdominal ultrasonography found at least two manifestations that could diagnose NFALD, including diffusely increased echogenicity (''bright'') liver with liver echogenicity greater than kidney or spleen, vascular blurring, and deep attenuation of ultrasound signal. 23…”
Section: Methodsmentioning
confidence: 99%
“…The covariates included age, sex, education level, per capita monthly income, marital status, smoking status, alcohol consumption, physical activity level, age at menarche, oestrogen replacement therapy status, parity, blood pressure, fasting blood glucose (FBG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), lowdensity lipoprotein cholesterol (LDL-C), and triglycerides (TG). Methods for assessing covariates have been described in a previous study [18]. Hypertension was diagnosed as a diastolic blood pressure ≥ 90 mmHg or systolic blood pressure ≥ 140 mmHg, use of antihypertensive drugs or a self-reported history.…”
Section: Covariatesmentioning
confidence: 99%
“…Therefore, the synergistic effect of GGT and SUA in MCI may be due to their effect on the risk of cardiovascular disease. In addition, a previous study found that increased SUA in women increases the risk of non-alcoholic fatty liver disease and that fatty liver disease development leads to increased GGT secretion, which might be an important reason for the parallel relationship between GGT and SUA levels (Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%